Understanding the Transfer of Writing Skills through the Writing Center: An Autoethnographic Account - Pandey, Hem Lal (Vox Batauli, 2024)
This paper explores the role of the writing center in facilitating writing in interdisciplinary contexts and the transfer of writing skills across academic disciplines. Drawing on my autoethnographic account of a university writing center consultant (writing tutor) at The University of Texas at El Paso (UTEP) and the psychological theories of learning transfer, I examine how the writing center functions as an academic space of a “contact zone” where writing skills are negotiated and transferred. A central question I address in this paper is: How does the writing center contribute to transferring writing skills across disciplines? This question revolves around the nature of interaction between consultants and student writers at the center involving the navigation through differences in disciplinary writing conventions, language, cultural backgrounds, academic mentoring, personal reading and writing experiences, and varying levels of exposure to academic writing practices. These encounters can result in transformative learning experiences for both tutors and student writers. I argue that the interdisciplinary nature of writing center consultations fosters the transfer of writing skills by creating opportunities for dialogue and negotiation between the consultants and the students of diverse disciplinary communities.